PUSAT PEMBELAJARAN DAN REKERASI MANADO. Eco-Friendly Building - Cheren K. Wattimena; Frits O.P. Siregar; Pierre H. Gosal (PS S1 Arsitektur. Jurusan Arsitektur, Fakultas Teknik Universitas Sam Ratulangi Manado, 2020)
In this revolutionary era where all human are in line with technological advances, where this as directly proportional to the interest in channeling people’s talents, of course, it requires a learning platform that can accommodate people’s hobbies as well as increasing human resources to be able to compete in this era. Several considerations were made in order to achieve the expectations of young people for this facility, especially the residents in Manado. Indequate demand and the lack of supply and in fact never existed in Manado, where these facilities support educational purposes in both academic and non-academic fields, as well as being a business opportunity for young businessmen, creating jobs and improving the quality of teaching and learning between teachers and students to achieve many goals in educational purposes as well as being a facilities that can bring joy to the people inside.With the theme of creating an eco-friendly building where this kind of architecture can bring so much impact in the neighborhood and also can help nature as it state in the process of bringing up such theme.Kata kunci :Pusat Pembelajaran, Pusat Rekreasi , Eco-Friendly Building.